Risk factors for adverse perinatal outcomes in imprisoned pregnant women: a systematic review - Plugge Emma; Knight Marian (BMC, 2005)
Abstract Background Imprisoned pregnant women constitute an important obstetric group about whom relatively little is known. This systematic review was conducted to identify the risk factors associated with adverse pregnancy outcome present in this group of women. Methods The review was conducted according to a prespecified protocol. Studies of any design were included if they described information on any of the pre-specified risk factors. We calculated the results as summary percentages or odds ratios where data was available on both cases and population controls. Results The search strategy identified 27 relevant papers of which 13 met the inclusion criteria, involving 1504 imprisoned pregnant women and 4571 population control women. Imprisoned women are more likely to be single, from an ethnic minority, and not to have completed high school. They are more likely to have a medical problem which could affect the pregnancy outcome and yet less likely to receive adequate antenatal care. They are also more likely to smoke, drink alcohol to excess and take illegal drugs. Conclusion Imprisoned women are clearly a high risk obstetric group. These findings have important implications for the provision of care to this important group of women.